Perjuangan penubuhan Negara Islam dalam era kebangkitan Islam di Malaysia dan Indonesia, 1982-2004 / Amin Fadlillah - Amin, Fadlillah (2017)

(untitled)
This thesis studies the struggle to establish an Islamic state In Indonesia and Malaysia. The idea of Islamic state was triggered by the phenomenon of Islamic resurgence for the period 1982 to 2004 of this study. Although there are differences in the conception, interpretation and mechanism on the definition of Islamic state, but the efforts initiated by political parties, Islamic and civil organizations towards the establishment of Islamic state have resulted in the implementation of Islam in education, economy, law, Islamic values and the strengthening the administrative machinery of the state. The methodology used in this study is qualitative method which based on written primary sources such as governmental documents, Islamic organizations, political parties and personal diaries. In addition, secondary sources such as books, articles and journal are also used. These sources also reinforced with interviews. Malaysia and Indonesia are chosen as the object of the study not only because both are major Islamic states in Southeast Asia, but also because there is a belief that the Islamic resurgence in these two countries will lead them to be the leaders of the Islamic world as an alternative to the Middle East region. 1982 was chosen as the beginning of the study because of the increasingly strong position of Mahathir Mohamad and Suharto after elections in both countries in the same year especially when Anwar Ibrahim joined UMNO in the same year, while in Indonesia, 1982 marked the improving relations between Islam and the government. 2004 was chosen as the limitation of the study based on event of the elections in the two countries which was a benchmark for the continuation of the struggle for an Islamic state. The findings show that the approach of conservative idealism attempted to establish an Islamic state idealism through the implementation of Islamic law comprehensively. The progressive approach idealizes the concept of Islamic state substantially and pragmatically with some considerations on existing constraints realistically. Secular group reject all forms of involvement and state intervention in the affairs of Muslim people because they believe the state should be strictly separated from the religion. Thus, the overall implementation of Islam in Malaysia and Indonesia in many areas affected by the approach of progressive faction. In the implementation of Islamic law, the approach used was to strengthen the provisions of Islamic law and the existing syariah courts. While in the field of education and economy are by setting up an institutional and legal system in line with Islamic principles. The change of orientation and commitment of the leaders in both countries also were the dominant factors in the rapid implementation of Islam in the period of this study. However, a significant difference between these two countries is the manifestation of the implementation of Islam in Malaysia is done formally. This is because the special position of Islam in the constitution, while in Indonesia is carried out by substantive. Thus, despite the open declaration by the government that Malaysia is an Islamic state and in Indonesia has never declared, but the fact that the two countries can be considered as Islamic states following the implementations of Islam in all aspects of life.